Direito à educação no contexto da universalização do ensino básico: estudo de caso da meta nº 3 do PNE baseado na abordagem em direito e política públicas - Pereira, Nathália Lima (2022)
The public policy established in goal nº 3 of the PNE is analyzed from the institutional legal point of view, aiming to understand to what extent the normative arrangement was effective in promoting the universalization of basic education in the country, which is the main instrument for the realization of the right to education with constitutional provision and currently governed by Law nº 13.005/2014. In order to obtain answers to the presented problematization, three specific questions were passed through, which make up the chapters of this study. Initially, we analyzed the evolution of the right to basic education in Brazilian constitutionalism, from Colonial Brazil to the 1988 Citizenship Charter; then, the influence of the National Education Plan was investigated as a public policy of the State responsible for promoting basic education in the country, especially among young people aged between 15 and 17 years, the target audience of the aforementioned action program; and finally, the conditions of effectiveness of the indicated policy were verified, using the frame of reference proposed by Maria Paula Dallarri, in order to give institutional legal vision to governmental action. Regarding the methodological aspects, regarding the collection of data, the research is bibliographic and documentary, in relation to the objectives, the study is characterized as descriptive, exploratory and explanatory, being of a qualitative and quantitative nature, as it intended to understand the normative scope in the implementation process of the program, for that, it was necessary to go through the statistical bias of the evolution of enrollments in the public network and expansion of the public service, between the years 2014 to 2021, with a hypothetical-deductive approach with a propositional bias, with a basic purpose. It was found that in the mentioned period, there were significant advances for the implementation of the action program, however without adequate proportion to attenuate the various regional inequalities regarding the expansion of the attendance of the school network, being necessary to promote changes in the institutional design, in order to to make goal nº 3 of the PNE more effective in the social field, through the creation of legal mechanisms of articulation that define clear guidelines for dialogue between the federative entities, especially through the institution of the National Education System (SNE).